Natural colloids at environmentally relevant concentrations affect the absorption and removal of benzophenone-3 in zebrafish. (1st October 2022) - Sun, Yu; Lu, Guanghua; Zhang, Peng; Wang, Ying; Ling, Xin; Xue, Qi; Yan, Zhenhua; Liu, Jianchao
Abstract: Aquatic natural colloids are closely related to the environmental behavior of pollutants, which may affect their bioavailability in aquatic organisms. This study explored the potential mechanisms of the natural colloids at environmentally relevant concentrations affecting the bioaccumulation process of benzophenone-3 (BP3) in zebrafish ( Danio rerio ). The results of kinetic model fitting showed that the natural colloids decreased the uptake and loss rate of BP3 by zebrafish but prolonged the time to reach the cumulative equilibrium, eventually resulting in a higher cumulative concentration in zebrafish. According to the tissue concentration at equilibrium and the results of toxicokinetic analysis, the presence of high molecular colloids could enhance the bioaccumulation of freely dissolved BP3 due to its high desorption rate with BP3 in the intestines of fish, increasing the freely dissolved BP3 concentrations to which zebrafish were exposed. Both natural colloids and BP3 could enhance the cell permeability of zebrafish, which allowed colloid-bound BP3 to directly enter the fish and accumulate in its muscle. Besides, although both natural colloids and BP3 could cause the metabolic disorders in adult zebrafish, they affected the physiological and biochemical activities of zebrafish through different pathways. The disturbance of glutathione metabolism in zebrafish induced by natural colloids may be the reason for the diminished ability of zebrafish to clear and transform BP3 in the mixture system. The carrier effect of natural colloids and reduced clearance ability of zebrafish eventually increased the bioaccumulation of BP3 in zebrafish. This study highlights the significance of natural colloids at environmentally relevant concentrations on the biological effects of emerging contaminants in actual waters, however, natural colloids are always ignored in most field investigation of pollutants, which would ultimately lead to an underestimation of the true ecological risk of pollutants. Graphical abstract: Image 1 Highlights: Natural colloids enhanced the bioaccumulation of freely dissolved and bound BP3. Both natural colloids and BP3 increased the cell permeability of zebrafish. Natural colloids induced more severe metabolic disturbance of zebrafish than BP3. The presence of natural colloids reduced the ability of zebrafish to clear BP3.